2013
DOI: 10.1525/sop.2013.56.2.287
|View full text |Cite
|
Sign up to set email alerts
|

State and Regional Suicide Rates: A New Look at an Old Puzzle

Abstract: U.S. suicide rates vary across the states and are higher in the American West than in other regions. Reasons for these patterns have eluded social scientists. This research note examines whether residential stability and population density as ecological contexts for social integration help explain the patterns. Refiecting Durkheimian reasoning, results suggest that residential stability helps explain both the high Western suicide rate and state suicide rates more generally. Final remarks address the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Residential stability is often measured using the portion of the population that has recently moved and the portion of housing that is renter-occupied housing (Cutchin and Churchill, 1999;Messer et al, 2006;Barkan et al, 2013). In an attempt to explain the east-to-west divide in suicide rates, one study found an association between residential instability and suicide rate (Barkan et al, 2013).…”
Section: Other Population Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Residential stability is often measured using the portion of the population that has recently moved and the portion of housing that is renter-occupied housing (Cutchin and Churchill, 1999;Messer et al, 2006;Barkan et al, 2013). In an attempt to explain the east-to-west divide in suicide rates, one study found an association between residential instability and suicide rate (Barkan et al, 2013).…”
Section: Other Population Characteristicsmentioning
confidence: 99%
“…Demographic variables included race, ethnicity, divorce, single parent homes, population density, and Rural-Urban Continuum Codes (RUCC) (Sen, 2004;Hempstead, 2006;Akhtar-Danesh and Landeen, 2007;Alegria et al, 2015;Fontanella et al, 2015;VanderWielen, et al 2015;Nestor et al, 2016). Residential stability was measured using renter-occupied homes and individuals living in a different home during the past twelve months (Cutchin and Churchill, 1999;Barkan et al, 2013). Latitude and mean annual global horizontal irradiance (GHI, kWh/m²/day) were used to explore the influence of climate and sunlight on help-seeking behavior for mental distress.…”
Section: County-level Explanatory Variablesmentioning
confidence: 99%
See 3 more Smart Citations